Attitude of Orthopaedic Surgeons to the E‑Patient: Experience from a Developing Country - Esan, Oluwadare; Oluwadiya, Kehinde Sunday; Popoola, Sunday Ogunsuyi; Babalola, Ranti O.; Alabi, Eyitayo O. (Nigerian Journal of Orthopaedics and Trauma, 2018)
Background: Increasingly, more patients are obtaining medical information from the Internet with which they are confronting their physicians. Very few studies have been reported from developing countries concerning physician’s attitude to such patients, and to our knowledge, none has been reported from Sub‑Saharan Africa. This study looked at the attitude of Nigerian orthopaedic surgeons to such patients. Methods: This was a questionnaire‑based interview of orthopaedic surgeons and their trainees at the 2013 annual conference of the Nigerian Orthopaedic Association in Lokoja, Nigeria. It was supplemented by an online Google form survey. Results: One hundred and twelve questionnaires were returned, and seven were incompletely filled and were discarded, leaving 105 for analysis. About 94.3% of the respondents have had previous encounters with e‑patients. The mean attitude score was high (3.64 ± 0.46, the highest obtainable was 5.0). Consultants and orthopaedists in semi‑urban settings scored higher than other categories. The physician’s self‑esteem and efficacy of using the Internet correlated highly with their attitude to e‑patients. Similarly, self‑esteem, the frequency of using the Internet and the experience of the way e‑patients have been presenting their information (print, verbal or electronic) were the significant predictors of physicians’ attitude to e‑patients. Conclusion: Orthopaedic surgeons and their trainees practising in Nigeria frequently encounter patients with Internet‑based medical information at consultations. Most of them have high positive attitudes towards these patients. There is a need for these doctors to become skilled in online information handling to become better at guiding such patients.